Ethnic Entrepreneurs, Crony Capitalism, and the Making of the Franco-Mexican Elite - Galindo Rodriguez, Jose (Book collections on Project MUSE., 2021)
"This work provides a new way to understand the scope and impact of crony capitalism on institutional development in Mexico. Beginning with the Porfiriato, the period between 1876 and 1911 named for the rule of President Porfirio Díaz, Jose Galindo identifies how certain behavioral patterns of the Mexican political and economic elite have repeated over the years, and analyzes aspects of the political economy that have persisted, shaping and at times curtailing Mexico's economic development. Strong links between entrepreneurs and politicians have allowed elite businessmen to receive privileged support, such as cheap credit, tax breaks, and tariff protection, from different governments and to run their companies as monopolies. In turn, successive governments have obtained support from businesses to implement public policies, and, on occasion, public officials have received monetary restitution. Galindo notes that Mexico's early twentieth-century institutional framework was weak and unequal to the task of reining in these systematic abuses. The cost to society was high and resulted in a lack of fair market competition, unequal income distribution, and stunted social mobility"--